Transferring managerial learning back to the workplace : the influence of personality and the workplace environment - Belling, Ruth (Cranfield University, 2000)
This thesis identifies the influences of individual characteristics, particularly psychological type preferences, and workplace environment features, on managers’ perceptions of the barriers and facilitators to transferring their learning from management development programmes. In doing so, it provides information and insights to help increase understanding of the transfer of learning process through the building of a model of transfer. Guided by a Realist perspective, this research was conducted using longitudinal survey methodology, incorporating both questionnaires and interviews. The survey gathered data at three time points, establishing a chronological ‘Base Map’ representing programme participants’ journeys through four kinds of learning event/experience, their expectations of those programmes, resulting learning outcomes and applications of learning back in their workplaces. This research identified 26 perceived barriers and 17 perceived facilitators to transfer of learning from 17 organisations, incorporating a wide range of workplace environments, described how these barriers and facilitators operate and identified the need to take the nature of the learning event/experience into account to provide a meaningful context for the transfer of learning outcomes. This research presents a series of ‘Route Maps’, highlighting the significant associations between individual characteristics, workplace features and elements of the learning and transfer processes, based on programme type. Psychological type was found to influence perceptions of barriers and facilitators to transfer and is associated with critical elements in the transfer process. This thesis contributes to theory and practice about transfer of learning from management development programmes and has implications for organisations, programme designers and future participants on such programmes.